Reconstruction of Sumang Customs in Gayo Community as An Effort to Prevent Underage Marriage - Suhartini, Suhartini; Surya, Achmad (Faculty of Law, Universitas Pekalongan, 2024)
Sumang custom in the Gayo community is an idea of cultural and religious values adopted by the community which is a reference for community behavior packaged in customary law. But at this time, Sumang shifted, faded, and even slowly disappeared its values in the Gayo community of Central Aceh Regency. The objectives of this study are: First, the nature of sumang customs in gayo society according to Indonesian positive law? Second, Factors for the fading of sumang customs in the Gayo community in Central Aceh district? This research is an empirical juridical research using primary data sources (field data) and secondary data obtained from primary legal materials, secondary legal materials and tertiary legal materials. Furthermore, the data obtained were analyzed in a qualitative descriptive manner. The results of the study explained, the nature of Sumang customs in the Gayo community as rules in manners and politeness that regulate the way of association of a man and a woman who is not his muhrim, which aims to avoid promiscuity and adultery. Factors of the fading of sumang customs in the gayo community, the lack of role of parents in introducing and teaching their children about sumang, due to technological advances, and the lack of functioning of supervisory roles carried out by Sarak Opat and bebujang (youth) in the village environment.